TINJAUAN HUKUM TERHADAP JAMINAN FIDUSIA YANG TIDAK DIDAFTARKAN PADA PEMINJAMAN KREDIT NON BANK - Mig Irianto Legowo (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2017)
Non-bank credit as a fiduciary institution formed on the basis of public need on debts (credit) with collateral without releasing the goods as collateral, because the goods / object is still used for business, to meet the needs of creditors. The credit agreement with fiduciary sometimes issues arise including fiduciary how if the object is lost or damaged, and how if the debtor defaults. The formulation of the problem in this research is how the legal review of the fiduciary is not registered in the non-bank credit lending? This study uses empirical juridical approach to the specification of analytical descriptive study, sampling was done by purposive sampling, data used included primary data consisting of field studies and secondary data includes the study of literature which was then analyzed qualitatively. As a recommendation of this study is that the government needs to work on improving the implementation of the fiduciary oversight on non-bank financial institutions in accordance with the regulations by-laws and regulations apply.